Negotiating Space and Security: The Sociocultural Role of Fences in Kapasan Chinese Settlements, Surabaya - Santoso, Dian Kartika; Junita, Sovie Nurmalia; Ramadiansyah, Faiz; Abidah, Darini Yusrina (Jurnal Arsitektur, 2025)
This study examines the sociocultural role of fences in the Kapasan Chinese settlements in Surabaya, Indonesia, focusing on their significance as physical and symbolic elements. Employing a qualitative case study approach, the research investigates how fences serve as boundaries, provide security, and reflect cultural identity within a multiethnic urban environment. Through field observations, interviews, and visual documentation, findings reveal that fences encapsulate historical resilience, cultural values, and adaptive responses to urban challenges. They act as protective barriers, markers of social status, and mediums for cultural expression. However, modernization and generational shifts pose challenges to preserving traditional designs. This research contributes to understanding the interplay between architecture, culture, and societal dynamics in multicultural settings.